(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the theoretical and methodological foundations for developing eco-literacy among students during the process of modernizing ecological education. It examines the pedagogical and psychological characteristics of modernizing ecological education, focusing on developing competencies related to eco-creativity, eco-responsibility, and eco-literacy, as well as the corrective influence of the relationship between nature and human beings. Additionally, the article analyzes the pedagogical and integrative aspects of forming eco-literacy in the modernization of ecological education.